2016
DOI: 10.1063/1.4967502
|View full text |Cite
|
Sign up to set email alerts
|

Quantum point contacts and resistive switching in Ni/NiO nanowire junctions

Abstract: Metal oxide devices that exhibit resistive switching are leading candidates for non-volatile memory applications due to their potential for fast switching, low-power operation, and high device density. It is widely accepted in many systems that two-state resistive behavior arises from the formation and rupture of conductive filaments spanning the oxide layer. However, means for controlling the filament geometry, which critically influences conduction, have largely been unexamined. Here, we explore the connecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Gao et al considered quantization in Ag/SiO 2 /In occurring at integer and half integer values of G 0 . Results pointing out in the same direction were also presented by a number of authors indicating that the idea of quantum conduction is more than a reasonable hypothesis. More conventional mechanisms such as Poole–Frenkel conduction and Schottky emission are also frequently invoked to model the high resistance state of SiO x films.…”
Section: Physical and Circuit Models Of Breakdown And Resistance Switmentioning
confidence: 86%
“…Gao et al considered quantization in Ag/SiO 2 /In occurring at integer and half integer values of G 0 . Results pointing out in the same direction were also presented by a number of authors indicating that the idea of quantum conduction is more than a reasonable hypothesis. More conventional mechanisms such as Poole–Frenkel conduction and Schottky emission are also frequently invoked to model the high resistance state of SiO x films.…”
Section: Physical and Circuit Models Of Breakdown And Resistance Switmentioning
confidence: 86%
“…These devices exhibited unipolar resistive switching that was ascribed to a thermochemical reduction/oxidation that gives rise to the formation/rupture of a conductive filament at the cross‐point junction. A more detailed analysis of Ni/NiO cross‐point junctions was later reported by Oliver et al that pointed out that the filament geometry in the cross‐point can be tuned by varying the electroforming process, allowing the creation of wide metallic or narrow semiconducting filaments as revealed by I – V – T measurements. The switching mechanism in Ni/NiO cross‐point junctions was further elucidated by real time TEM investigation of filament creation/rupture by Ting et al that directly observed morphological changes at the cross‐junction point as a consequence of the oxygen ions migration that is responsible for the evolution of the conductive filament.…”
Section: Resistive Switching In Nanowire Random Networkmentioning
confidence: 96%
“…Devices which displayed memristive loops also had small nonlinearities around low voltages, in line with recent reports and suggesting the filaments formed in the nanowire junctions are truly metallic. [40] These nonlinearities are expected given that most of the junctions will be Ni/Ni, with relatively few Ni/Ag junctions containing both an oxide and a polymer capacitive layer, and Please do not adjust margins Please do not adjust margins very few Ag/Ag junctions. Further addition of Ag nanowires will eventually lead to a network which is effectively no longer a heterogeneous Ni/Ag hybrid but a very sparse self-selected Ag nanowire network.…”
Section: Resultsmentioning
confidence: 99%